PERANAN PERUSAHAAN DALAM MENINGKATKAN KEMAMPUAN KERJA PETERNAK DAN KUALITAS HASIL PANEN MADU DI MASA PANDEMI - Agustini, I Gusti Ayu Ari (E-Jurnal Manajemen; Vol 9 No 12 (2020)DO - 10.24843/EJMUNUD.2020.v09.i12.p05, 2020)
The Covid-19 pandemic has undeniably crippled the economy of the wider community. Beekeeping and its derivatives business are promising efforts during the current pandemic. Honey, which is one of its derivative products, has become a necessity that is most in demand by the public to maintain stamina and endurance. Currently the market demand for good quality honey is getting bigger, so that this opportunity is widely exploited by honey business actors. The purpose of this study was to analyze the efforts made by Bali Honey in improving the working ability of honey breeders in the midst of the Covid-19 pandemic and to analyze the strategies implemented to improve the quality of the honey harvest to bring benefits to the local community. The data analysis method is descriptive qualitative. Data analysis was carried out by collecting secondary data and primary data. The data and information obtained through field research are then analyzed by doing data reduction, namely summarizing the data from interviews and field observations, then interlinking them with the theoretical basis and literature review to get a final conclusion. The theoretical foundations used in the research are reinforcement theory, expectancy theory, and goal setting theory. The result of the research is that consistent education carried out by Bali Honey plays an important role in improving the working ability of honey farmers so that the quality of the yields produced can compete in the market. Keyword : the role of the company, work ability, product quality